Escuta ética e protagonismo infantil em contextos de violência contra crianças: uma análise da produção acadêmica - Soares, Denise Gomes (Universidade Federal de São Carlos, 2022)
The objective of this dissertation was to analyze the way in which ethical listening is put on the agenda in research that addresses violence against children, considering Baruch Spinoza's concept of Ethics, which is based on relationships and affections. It starts from the theoretical framework of Sociology of Childhood, which focuses on children as protagonists, with specific rights that fall within the dimensions of Provision, Protection, and Participation. From this point of view, the existing impasse between Protection and Participation is problematized, especially with regard to contexts of violence against children. That is, we evaluated if the children’s rights are being respected in research cases that address violence against children. This research is bibliographical in nature, based on a collection of documents retrieved from the UNICEF, SciELO, Redalyc, and Anped databases, as well as a number of books and thematic dossiers containing articles and concept entries, with aims to raise and analyze the discussions that fall within two central axes: ethical listening and violence against children. Results show that, when discussing ethical listening with children and adults who suffered situations of violence during childhood, in the Health area, the guidelines are more related to resolution 466/2012, confidentiality, and the Free and Informed Consent Term. These are important requirements for the Research Ethics Committee, but they do not have many specifications about under which circumstances these researches are carried out. In research in the area of Education/Sociology of Childhood, discussions about listening go beyond the requirements of the Ethics Committee. There is also a discussion about the intervention of the researcher in the field and how they can build a trusting relationship with children. However, in cases involving the theme of violence, the discussion requires care. We present some possible propositions based on reflections of the researched authors on what should be considered in a research with children, namely when we are referring to the ethics of research with children in situations of violence. The propositions presented at the end of this dissertation are: to use secondary elements; to not rely on assumptions and stereotypes; to exercise specialized listening; to mobilize the family in specific circumstances, and to go beyond protocol ethics. The importance and timeliness of this debate is highlighted, both in the sense of expanding it, and in the sense of bringing subsidies to guarantee the fulfillment of the fundamental rights of children, especially those who are victims of violence, to the same extent that we expand listening ethics, with the children and for the children.
Ethical listening and child protagonism in contexts of violence against children: an analysis of academic production
Keywords: Infância(s)/criança(s); Violência contra crianças; Ética de pesquisa; Sociologia da infância; Escuta; Childhood/children; Violence against children; Ethics in research; Sociology of childhood; Listening; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO; CIENCIAS HUMANAS::PSICOLOGIA::PSICOLOGIA EXPERIMENTAL::ESTADOS SUBJETIVOS E EMOCAO; CIENCIAS DA SAUDE::SAUDE COLETIVA::SAUDE PUBLICA; CIENCIAS SOCIAIS APLICADAS::SERVICO SOCIAL::SERVICO SOCIAL APLICADO::SERVICO SOCIAL DA EDUCACAO